2019
DOI: 10.1515/labmed-2019-0046
|View full text |Cite
|
Sign up to set email alerts
|

Macroprolactin: an overlooked reason of hyperprolactinemia

Abstract: Background Immunoassays show variability in the detection of macroprolactin. The aim of this study was to detect the frequency of macroprolactinemia in hyperprolactinemic patients and the problems encountered in routine clinical practice. Methods The screening of macroprolactinemia was performed by precipitation with polyethylene glycol (PEG) in 900 patient samples with hyperprolactinemia over a period of approximately 6 months. Recovery values of less than 40% and greater than 60% were considered as macropro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This could be due to a higher number of female patients being investigated for infertility and menstrual disturbance than men who are only being investigated for sexual dysfunction [69,90]. Subgroup analysis also did not show any difference in prevalence estimate based on age group, similar to other previous studies [49,88]. However, several other studies reported that the prevalence of mPRL tends to increase with advancing age [36,86].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This could be due to a higher number of female patients being investigated for infertility and menstrual disturbance than men who are only being investigated for sexual dysfunction [69,90]. Subgroup analysis also did not show any difference in prevalence estimate based on age group, similar to other previous studies [49,88]. However, several other studies reported that the prevalence of mPRL tends to increase with advancing age [36,86].…”
Section: Discussionsupporting
confidence: 73%
“…A lower prevalence estimate was observed among studies involving both sexes than studies involving only female participants. Findings from previous studies regarding the matter are inconclusive, with some studies reporting no difference in the prevalence of mPRL between sex [77,[86][87][88]. In contrast, some other studies reported a higher prevalence of mPRL among females than males [35,36,51,89].…”
Section: Discussionmentioning
confidence: 97%
“…Macro-PRL consists of monomeric PRL complexed with immunoglobulins. Most macro-PRL (87%) is composed of monomeric PRL complexed with IgG ( 3 , 9 , 17 , 18 ). Within this category of PRL-IgG complexes, the majority (67%) involve anti-PRL autoantibodies ( Fig.…”
Section: Macroprolactin Structurementioning
confidence: 99%
“…In fact, a recent study by Muhtaroglu et al. ( 17 ) found that of 5,007 consecutive serum samples evaluated for PRL, 900/5,007 (17.9%) had elevated PRL levels, and providers requested macro-PRL screening for only 171/900 (19.0%) samples. Of the 171 patients who underwent screening for macro-PRL with polyethylene glycol (PEG), 31 were diagnosed with macroprolactinemia ( 17 ).…”
Section: Diagnosing Macroprolactinemiamentioning
confidence: 99%
See 1 more Smart Citation